Pterostilbene supplementation inhibits early inflammatory response and oxidative stress in UVB-induced BALB/C mice - Tava Shelan Nagapan,; Lim, Wenna Nallance; Ahmad Rohi Ghazali,; Dayang Fredalina Basri, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Extended dermal exposure of ultraviolet B (UVB) can induce erythema, hyperpigmentation, epidermal hyperplasia and cancer. Natural active compound such as pterostilbene (PS) is a potential UV-protecting agent as it has broad biological activities. This study aimed to evaluate the photoprotective effect of pterostilbene on ultraviolet-B-induced BALB/c mice. Twenty-four female mice were randomised into four groups (n=6/group): vehicle control (VC); UVB irradiated only (UVB only); UVB irradiation treated with pterostilbene 10 mg/kg (PS10+UVB); (iv) UVB irradiation treated with pterostilbene 20 mg/kg (PS20+UVB). The PS treatments were given for 14 days, and UVB was given at dose 250 mJ/ cm2 on days 9, 11, and 13 of the treatment periods. The results showed that PS lessened redness and scaling on the skin of UVB-irradiated mice. The skinfold thickness and epidermal thickness in the PS-treated group were significantly reduced (p<0.05) in comparison with those in the UVB only group. The PS10 and PS20 groups (5.927 ± 0.354 and 5.660 ± 0.765 nmol/g, respectively) demonstrated significantly decreased MDA levels (P<0.05) relative to the UVB only group (13.343 ± 1.350 nmol/g). The GSH level in both PS10 (0.555 ± 0.020 µmol/mg) and PS20 (0.568 ± 0.055 µmol/mg) groups increased significantly (p<0.05) compared with that in the UVB only group (0.376 ± 0.025 µmol/mg). SOD activity in the PS20 group (1.388 ± 0.172 U/min/mg) increased significantly (p<0.05) compared with that in the UVB only group (0.561 ± 0.034 U/min/mg). Histological observation showed that PS reduced leukocyte infiltration and epidermal hyperplasia. Hence, oral PS may exert a photoprotective effect by acting as an anti-inflammatory and antioxidant agent on UVB-irradiated mice skin.